Just war thinkers from Cicero to the 21st century - Brunstetter, Daniel R.; O'Driscoll, Cian (War, conflict and ethics, 2018)
This volume offers a set of concise and accessible introductions to the seminal figures in the historical development of the just war tradition. In what, if any, circumstances are political communities justified in going to war? And what limits should apply to the conduct of any such war? The just war tradition is a body of thought that helps us think through these very questions. Its core ideas have been subject to fierce debate for over 2,000 years. Yet they continue to play a prominent role in how political and military leaders address the challenges posed by the use of force in international society. Until now there has been no text that offers concise and accessible introductions to the key figures associated with the tradition. Stepping into this breach, Just War Thinkers provides a set of clear but detailed essays by leading experts on nineteen seminal thinkers, from Cicero to Jeff McMahan. This volume challenges the reader to think about how traditions are constituted-who is included and excluded, and how that is determined-and how they serve to enable, constrain, and indeed channel subsequent thought, debate, and exchange